Plasma-Derived Exosomal SncRNA as a Promising Diagnostic Biomarker for Early Detection of HBV-Related Acute-on-Chronic Liver Failure - Xu, Wenli; Yu, Mingxue; Wu, Yuankai; Jie, Yusheng; Li, Xiangyong; Zeng, Xinxin; Yang, Fangji; Chong, Yutian (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The small non-coding RNAs (sncRNAs) including mircoRNAs and the non-canonical sncRNAs (i.e., tRNA-derived small RNAs [tsRNA] and rRNA-derived small RNAs [rsRNA]) are a vital class of gene regulators in responses to a variety of diseases. We focus on a sncRNAs signature enriched in hepatitis V virus (HBV)-related acute-on-chronic liver failure (ACLF) for developing a plasma exosomes-based non-invasive biomarker for human ACLF. Methods: In this work, sncRNAs related to HBV-ACLF were identified by small RNA-seq in plasma exosomes collected from 3 normal subjects, 4 chronic hepatitis B (CHB) patients with flare and 6 HBV-ACLF patients in the discovery cohort. Thereafter, the differentially expressed sncRNAs were further verified in validation cohort (n=313) using the newly developed molecular signature incorporating different mi/ts/rsRNAs (named as MTR-RNA) through qRT-PCR assays. Subsequently, using the LASSO logistic regression (LR) model analysis, we developed a MTR-RNA classifier for early dectection of ACLF. Results: The identified sncRNAs (hsa-miR-23b-3p, hsa-miR-223-3p, hsa-miR-339-5p, tsRNA-20, tsRNA-46 and rsRNA-249) were specifically differentially expressed in plasma exosomes of HBV-ACLF. The MTR-RNA signature (AUC=0.787) containing the above sncRNAs distinguished HBV-ACLF cases among normal subjects with 71.67% specificity and 74.29% sensitivity, CHB patients with flare (AUC=0.694, 85.71% sensitivity/59.5% specificity), and patients with CHB/cirrhosis (AUC=0.785, 57.14% sensitivity/94.59% specificity). Notably, it revealed 100% specificity/94.80% sensitivity in detecting patients or normal people. Conclusions: Our as-constructed plasma-derived exosomal sncRNAs signature can serve as a reliable biomarker for ACLF detection and also be adopted to be the pre‑triage biomarker for selecting cases that can gain benefits from adjuvant treatment.